CHARACTERISTICS OF EDUCATIONAL STANDARD DEVELOPMENT IN INFORMATICS (TRAINING DIRECTION 0403020) ﻿ (Journal of Information Technologies in Education (ITE), 2010)
In the paper main principles of development and structure of educational standard in the direction 040302 INFORMATICS are described.
Keywords: branch standard; informatics; IT-specialist; training direction